The Role of Religious Activities in Maintaining the Solidarity and Cultural Identity of the Batak Toba Community in Ambon - Devi M. Sembiring; Aholiab Watloly; Suleman Watianan (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the role of religious activities in maintaining social solidarity and preserving the cultural identity of the Batak Toba community in Ambon amid social change, migration, and increasing cultural diversity. The research aims to analyze how collective religious practices function not only as spiritual expressions but also as social and cultural mechanisms that strengthen community cohesion and reinforce ethnic identity among Batak Toba migrants. The study employed a qualitative descriptive approach through in-depth interviews, participant observation, and documentation involving community leaders, church members, and Batak Toba families residing in Ambon. Data were analyzed thematically to identify patterns of interaction, cultural transmission, and collective values embedded in religious activities. The findings reveal that religious gatherings, worship services, traditional church events, and faith-based communal celebrations play a significant role in fostering mutual support, strengthening kinship networks, and preserving Batak Toba cultural traditions, including language use, customary values, and collective rituals. Religious activities also function as adaptive spaces that enable the community to negotiate cultural identity within a multicultural urban environment. The novelty of this study lies in its emphasis on the integration of religion, migration, and ethnic identity preservation within the context of an urban multicultural society in Eastern Indonesia. The study concludes that religious activities serve as an important socio-cultural instrument for sustaining solidarity and cultural continuity among migrant communities. It recommends strengthening community-based religious and cultural programs as part of broader social and political efforts to promote multicultural harmony, social integration, and cultural resilience in diverse societies.